Development of Positive Communication Skills: Literature Review - Navylia Tirta Kencana; Amanda Nadia Adjani; Aurel Shifa Salsabilla; Niken Angraini (International Conference on Psychology and Education (ICPE), 2023)
This study aims to determine the development of positive communication skills. This study used a qualitative method in the form of a literature review. The samples in this study were 16 scientific references in the form of 9 books on communication and 7 scientific journal articles that discussed communication. Data collection techniques were carried out using an online search engine by entering communication keywords and additional keywords that were close. Scientific references are selected based on suitability with the criteria and limitations in this study. The results of the study state that positive communication can be developed effectively in various ways, namely understanding, pleasure, influencing attitudes, good social relations, and action.